Model Pengembangan Budaya Mutu dalam Pembelajaran Pendidikan Agama Islam di Padangsidimpuan - Zulhimmah, Zulhimmah; Zunidar, Zunidar (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
This study aims to determine the model of developing a quality culture in PAI learning at Nurul Ilmi Private Junior High School Padangsidimpuan. In detail, the objectives of this study are: 1) to find out the model program for developing a quality culture of Islamic Religious Education learning at the Nurul Ilmi Private Junior High School, 2) the implementation of the quality culture development model program in Islamic religious education learning at the Nurul Ilmu Padangsidimpuan Middle School, 3) the involvement of personnel resources. implementation of a quality culture development model program in Islamic religious education learning at SMP Nurul Ilmu Padangsidimpuan.To obtain the data needed in this study, interview, observation, and documentation techniques were used. Meanwhile, to analyze the data used data reduction procedures, data exposure and drawing conclusions. The process of analyzing research data is triangulation of data by cross-checking between interview, observation and documentation methods. In addition, cross-examination of data sources, from school principals, vice principals, administration, teachers of Islamic religious subjects, and students.